Micropolitics in collective learning spaces for adaptive decision making - and Tschakert, Petra; Das, Partha Jyoti; Shrestha Pradhan, Neera; Machado, Mario; Lamadrid, Armando; Buragohain, Mandira; Hazarika, Masfique Alam (Global Environmental Change, 2016)
Recent advances on power, politics, and pathways in climate change adaptation aim to re-frame decision-making processes from development-as-usual to openings for transformational adaptation. This paper offers empirical insights regarding decision-making politics in the context of collective learning through participatory scenario building and flexible flood management and planning in the Eastern Brahmaputra Basin of Assam, India. By foregrounding intergroup and intragroup power dynamics in such collective learning spaces and how they intersect with existing micropolitics of adaptation on the ground, we examine opportunities for and limitations to challenging entrenched authority and subjectivities. Our results suggest that emancipatory agency can indeed emerge but is likely to be fluid and multifaceted. Community actors who are best positioned to resist higher-level domination may well be imbricated in oppression at home. While participatory co-learning as embraced here might open some spaces for transformation, others close down or remain shut.
Keywords: Co-learning; Flood management; Participatory scenarios; Politics of adaptation; Power